2008
DOI: 10.5704/moj.0811.006
|View full text |Cite
|
Sign up to set email alerts
|

Distal Radius Morphometry in the Malaysian Population

Abstract: The goal of treatment in distal radius fracture is to restore the anatomy of the distal radius, however the criteria currently used to evaluate the quality of reduction are based on Western based published figures. This goal of this study was to investigate whether there are variations in the morphology of the distal radius among the multiracial population of Malaysia. Consecutive normal wrist radiographs of patients who presented to the accident and emergency unit in three major hospitals in Malaysia were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 17 publications
5
33
4
2
Order By: Relevance
“…We found the mean length of radius, length of radial styloid process, transverse and oblique width of distal end, and the AP diameter of distal end as 23. 12 [14][15][16][17] In our study, we got the angle of radial inclination as 25.05°, which was almost similar to the values obtained by Chan et al, Gartland and Werley, and Schuind et al…”
Section: Discussionsupporting
confidence: 78%
“…We found the mean length of radius, length of radial styloid process, transverse and oblique width of distal end, and the AP diameter of distal end as 23. 12 [14][15][16][17] In our study, we got the angle of radial inclination as 25.05°, which was almost similar to the values obtained by Chan et al, Gartland and Werley, and Schuind et al…”
Section: Discussionsupporting
confidence: 78%
“…Chan et al found that ulnar variance was statistically variable (significant) in the Chinese and Malaysian population [2]. Hadi et al studied that there was a statistically significant difference in the radial height, inclination, palmar tilt and ulnar variance between the male and female subjects of the Indonesian population [9].…”
Section: Introductionmentioning
confidence: 99%
“…Distal radius morphometry is extremely critical for normal wrist biomechanics, which has been studied and reported before. Radial height, radial inclination, palmar tilt and ulnar variance are the four important parameters to describe the distal radius morphometry [2]. Short WH et al, in their experimental cadaveric study described the importance of reduction in the palmar tilt, leading to increased dorsal angulation, results in increased loading of the distal radioulnar joint due to increased contact pressure on the articular surface between the sigmoid notch and ulnar head [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations